ANALISIS STRATEGI MAHASISWA PGSD KELAS 1C DALAM MEMBANGUN KARAKTER SEBAGAI CALON GURU - Neril Hidayatun Nikmah; Nabilla Prestiana Ekayanti; Seftiana Rofiatul Rozah; Rian Damariswara (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2025)
The personality skills that owned by a teacher play a crucial role in achieving educational goals. This personality is shaped by individual experiences, which govern one's perspective and thinking, and are reflected in behavior and accumulated in personality. This study shows that character education is essential in preparing students to become good teachers. In this regard, efforts and strategies are needed to develop good character in order to become a professional teacher. A professional teacher is not only one who relies on knowledge but also on moral qualities and must cultivate the values of a professional teacher's character. This study uses a qualitative descriptive method with primary data sources consisting of interviews and surveys, and secondary data from literature reviews. The purpose of this research is to understand the strategies of first-year PGSD students in the 1C class at Universitas Nusantara PGRI Kediri in forming and developing character as future teachers. The research method uses a qualitative descriptive approach. The results of this study indicate a high level of interest and understanding among the 1C class students of Universitas Nusantara PGRI Kediri to become teachers who not only understand but also can implement teaching skills. The implications of this study can be used for further research development.